Introducing phonetics and phonology - Davenport, Michael, 1954-; Hannahs, S. J. (Routledge, 2020)
"Intended for the absolute beginner, Introducing Phonetics and Phonology requires no previous background in linguistics, phonetics or phonology. Starting with a grounding in phonetics and phonological theory, the book provides a base from which more advanced treatments may be approached. It begins with an examination of the foundations of articulatory and acoustic phonetics, moves on to the basic principles of phonology, and ends with an outline of some further issues within contemporary phonology. Varieties of English, particularly Received Pronunciation and General American, form the focus of consideration, but aspects of the phonetics and phonology of other languages are discussed as well. This new edition includes: revised exercises and examples; additional coverage of typology, autosegmental phonology, and articulatory and acoustic phonetics; broader coverage of varieties that now features Australian English; and an extended chapter 7 that includes more information on the relationship between phonetics and phonology. Introducing Phonetics and Phonology 4th Edition remains the essential introduction for any students studying this topic for the first time. This new edition has been revised and updated throughout in light of advances in the field, without compromising the overall aims of the text: to provide an accessible introduction to phonetics and phonology"--